Let the length of the shorter leg is x.
The length of the the longer leg will be (x+3) m.
The length of the hypotenuse will be (x+6) m.
Applying the pythagorus theorem,
![\begin{gathered} (x+6)^2=x^2+(x+3)^2 \\ x^2+36+12x=x^2+x^2+9+6x \\ x^2-6x-27=0 \\ x^2-9x+3x-27=0 \\ x(x-9)+3(x-9)=0 \\ (x-9)(x+3)=0 \\ x=9\text{ \& -3} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5ww04bla0c0c2l9753u4l4pcdl3o1eyjlz.png)
Neglecting the negative value of x.
Length of the shorter leg: 9 cm
Length of the longer leg: 9+3 cm=12 cm
Length of hypotenuse: 9+6 cm= 15 cm.